Classifying radiographic changes of the pubic symphysis in male athletes: Development and reproducibility of a new scoring protocol. Issue 134 (January 2021) - Serner, Andreas; Arnaiz, Javier; Mosler, Andrea; Almusa, Emad; Vuckovic, Zarko; Tak, Igor; Maas, Mario; Weir, Adam; Hölmich, Per
Highlights: We developed a well-defined radiographic scoring protocol for the pubic symphysis in three stages. This protocol showed moderate to almost perfect intra-rater reproducibility, and fair to substantial inter-rater reproducibility. The protocol can assist in the clinical assessment, and provides basis for further advances in radiographic assessment of the pubic symphysis. Abstract: Purpose: To develop a specified radiographic scoring system for the pubic symphysis and adjacent bones, and to examine the intra- and inter-rater reproducibility of this system. Method: Development of the scoring protocol was performed in three stages using AP pelvis radiographs of 102 male adult athletes. The final protocol included 5 overall scoring items, which included further specification of locations: 1) bone lucency (erosion-like configuration and cysts), 2) proliferation, 3) fragmentation, 4) sclerosis, and 5) joint space width. Intra- and inter-rater reproducibility were determined using Cohen's kappa statistic (κ) and intraclass correlation coefficient (ICC). The standard error of measurement (SEM) and minimal detectable difference (MDD) were also determined. Results: We present a radiographic scoring protocol with clear definitions and examples to improve clinical usability. Intra-rater reproducibility was: bone lucency (erosion-like configuration or cysts): κ = 0.67 (95 %CI 0.56−0.78), proliferation: κ = 0.54 (95 %CI 0.38−0.70), fragmentation: κ = 0.80 (95 %CI 0.67−0.93), sclerosis: κ = 0.60 (95 %CI 0.49−0.71), and joint space width: ICC(2.1) 0.85 (95 %CI 0.78−0.89), SEM 0.4 mm, MDD 1.2 mm. Inter-rater reproducibility was: bone lucency: κ = 0.61 (95 %CI 0.50−0.72), proliferation: κ = 0.34 (95 %CI 0.20−0.48), fragmentation: κ = 0.67 (95 %CI 0.50−0.84), sclerosis: κ = 0.30 (95 %CI 0.17−0.43), and joint space width: ICC(2.1) 0.72 (95 %CI 0.59−0.81), SEM 0.5 mm., MDD 1.5 mm. Conclusions: The Aspetar pubic symphysis radiographic scoring protocol contains five overall scoring items, with additional specifications. These five items showed moderate to almost perfect intra-rater reproducibility, and fair to substantial inter-rater reproducibility. This protocol provides the basis for use in clinical practice, and will allow future investigations of the clinical significance of radiographic changes at the pubic symphysis in athletes.